PENGARUH BERMAIN ORIGAMI TERHADAP PERKEMBANGAN MOTORIK HALUS DI KELOMPOKÂ BTK DHARMAWANITADESA WONOKUSUMO MOJOSARI MOJOKERTOÂ - Prasastia Lukita Dewi, Catur; Dwi Latifah, Nikmatul (JURNAL KEPERAWATAN SEHAT, 2016)
Origami is an art of paper folding resulting in a variety of shapes, for example shapes of animals, flowers or transportation. Origami can hone fine motor skills through the fingers of the hands of children while folding the paper. The purpose of this research was to analyze the effect of play origami on the development of motor skills in students in kindergarten Dharmawanita group B Wonokusumo village Mojosari District of Mojokerto. This study design is pre experiment with the approach of one group pretest-posttest design. Variable research is giving the game origami as an independent variable and development motoric skills of preschool children as the dependent variable. The research population is the whole student group B TK Dharma Wanita Wonokusumo village Mojokerto as many as 42 respondents. Samples were collected by use purposive sampling as many as 26 children. Data collected use the instrument DDST, before and afther to gived origami game, then analyzed editing, coding, scoring and tabulating and tested with the Wilcoxon test. Wilcoxon test results showed α = 0.05 and ρ = 0,020 research results show that ρ <α so that H1 is accepted then there is the effect of origami game to the development of development motoic skills of preschool-aged children. Children who get a lot of stimulation or stimulation given to improve child development well stimulation was obtained from teachers or teachers of the facilities provided by the school, one of kind with origami game that same as with age of children and can stimulate the development of children with varians of models and form so that can train childrens ability to concentrate and kratifitas.Keywords: development motoic skills, preschoolers origami